2020
DOI: 10.1111/jep.13393
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration in Australian residential aged care: A time‐and‐motion study

Abstract: Rationale/aim Medication administration is a complex and time‐consuming task in residential aged care facilities (RACFs). Understanding the time associated with each administration step may help identify opportunities to optimize medication management in RACFs. This study aimed to investigate the time taken to administer medications to residents, including those with complex care needs such as cognitive impairment and swallowing difficulties. Method A time‐and‐motion study was conducted in three South Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…This study has several strengths, including applying the structured and validated WOMBAT methodology and ensuring exact collection of observed task time applying several observation categories simultaneously [ 24 ]. Also, the meticulously developed observation categories, the inter-rater validation, and the number and duration of the observations strengthen the internal validity of our findings [ 38 , 39 , 40 ]. The limitations include observation bias due to the Hawthorne effect, i.e., people changing their behavior when they know they are being watched.…”
Section: Discussionsupporting
confidence: 67%
“…This study has several strengths, including applying the structured and validated WOMBAT methodology and ensuring exact collection of observed task time applying several observation categories simultaneously [ 24 ]. Also, the meticulously developed observation categories, the inter-rater validation, and the number and duration of the observations strengthen the internal validity of our findings [ 38 , 39 , 40 ]. The limitations include observation bias due to the Hawthorne effect, i.e., people changing their behavior when they know they are being watched.…”
Section: Discussionsupporting
confidence: 67%
“…Pharmacotherapeutic complexity can be assessed considering numerous factors, but the complexity index is one of the few methodologies capable of numerically quantifying this criterion [36,45,46] and is validated for Portuguese [36]. Studies from Brazil and Portugal reported similar MRCI means to the one in our data, while Australian studies found higher complexity [47][48][49][50]. The MRCI is instrumental in gauging the challenge each pharmacotherapeutic profile presents, and our findings corroborate a direct correlation between MRCI values, the number of medications, and patient age [49,51].…”
Section: Discussionsupporting
confidence: 53%
“…Medication management is a significant component of direct care activities in RACFs and reducing time spent administering medications may enable staff to shift a meaningful period of time to other care activities or spend more time on other medication safety initiatives [40]. Previous studies have identified that time spent on medication rounds by nurses varies from approximately 1 h for 20 residents, to 4.5 h for 35 residents [43][44][45]. Data from three RACFs participating in the SIMPLER study suggests nurses spend an average of five minutes administering medications per resident per round [45].…”
Section: Clinical Significancementioning
confidence: 99%
“…Previous studies have identified that time spent on medication rounds by nurses varies from approximately 1 h for 20 residents, to 4.5 h for 35 residents [43][44][45]. Data from three RACFs participating in the SIMPLER study suggests nurses spend an average of five minutes administering medications per resident per round [45]. Extrapolation of the reduction in the average number of administration times for regular medications observed at 4 month follow up suggests 85 h of staff time could be redistributed per month in a 100 bed RACF.…”
Section: Clinical Significancementioning
confidence: 99%